THE EFFECT OF JOB INSECURITY ON MULTIDIMENTIONAL FATIGUE DUE TO WORK IN ENGINEERING SUPPORTING WORKERS FOR POWER PLANT REPAIR SERVICES - Faren Rizka Samara; Dewi Kurniasih; Farizi Rachman (Department Statistics, Faculty Mathematics and Natural Science, UNIMUS, 2023)
Power Plant Repair Service Engineering Supporting Workers are workers who provide service solution services such as Maintenance and Overhaul of power plants. In practice, work placements tend to move according to the needs of the maintenance schedule, as well as the demands for completion of work which tend to be short resulting in continuous overtime work during the work period. Based on the results of measuring psychological factors in 2022 at work, it is known that workers have an excess of quantitative and qualitative burdens and role ambiguity as the dominant triggersv that cause work stress/burnout/fatigue. From the explanation above, there is a potential indication of multidimensional fatigue due to work which is hypothesized to have a influence with job insecurity. This study aims to analyze whether or not there is a influence between latent variables in this case job insecurity on multidimensional fatigue through the AMOS Structural Equation Modeling (SEM) method in order to obtain overall test results for the constructs tested. The test results show that Job Insecurity has a significant effect on all indicators (Concerns About Transferring to Another Job (JI1), Concerns About Changes in Job Descriptions (JI2), Concerns About Work Schedules (JI33), Concerns About Decreases in Salary (JI4) and Concern About Job Prospects (JI5)) with (p-value = 0.001) and Job Insecurity have a significant effect on Multidimensional Work-related Fatigue (p-value = 0.001)